Constitutionalizing world politics : the logic of democratic power and the unintended consequences of international treaty making / Karolina M. Milewicz. - Milewicz, Karolina (Cambridge University Press, 2020)
The elusive ideal of a world constitution is unlikely to be realized any time soon - yet important steps in that direction are happening in world politics. Milewicz argues that international constitutionalization has gathered steam as an unintended by-product of international treaty making in the post-war period. This process is driven by the logic of democratic power, whereby states that are both democratic and powerful - democratic powers - are the strongest promoters of rule-based cooperation. Not realizing the inadvertent and long-term effects of the specialized rules they design, states fall into a constitutionalization trap that is hard to escape as it conforms with their interests and values. Milewicz's analysis will appeal to students and scholars of International Relations and International Law, interested in international cooperation, as well as institutional and constitutional theory and practice.